Trump’s Second Term and the Return of ‘America First’: Continuity, Institutions, and Global Impact in 2025 - Widyantoro, Sigid Widyantoro (Global and Policy Journal of International Relations, 2026)
This study examines the continuity and transformation of United States foreign policy under Donald Trump’s second administration in 2025, focusing on three dimensions—policy continuity, institutional response, and global impact. Using a qualitative, library-based approach and applying neorealist, liberal, and constructivist frameworks, the research analyzes decisions such as the U.S. withdrawal from the Paris Climate Accord, disengagement from the World Health Organization, and the “Liberation Day” tariff initiative. Findings reveal that Trump’s policies demonstrate ideological persistence rather than strategic innovation, reaffirming the primacy of sovereignty and unilateralism in American foreign policy. While domestic and international institutions voiced opposition, their material constraints limited any effective resistance, confirming the neorealist logic of state dominance. However, partial liberal and constructivist resilience remains evident in adaptive institutional behaviors and evolving global norms. The study concludes that Trump’s 2025 foreign policy contributes to the transition from a liberal international order toward a pluralist, ideologically contested system, where cooperation endures amid renewed great-power competition.